An analysis of the justification of the stringent natural person insolvency law system in South Africa in light of the "advantage to creditors" requirement - Van Wyk, Jani Sani (University of Pretoria, 2021)
Dissertation (LLM (Insolvency Law))--University of Pretoria, 2020.